Circumventing Censorship Restrictions: Actors as Warriors and Warriors as Actors in Ukiyo-e Prints - Varshavskaya, Elena Yu. (Actual Problems of Theory and History of Art, 2022)
Ukiyo-e prints, a vibrant form of mass-produced urban art of Edo period Japan were subject to official regulations. Thematic and technical control imposed by the Tokugawa government over the printed material, however, only spurred the imagination of the artists in their efforts to bypass censorship restrictions. This paper focuses on two case studies in which the theater topic, central to the art of ukiyo-e, was involved in secret conversation between the designers of prints and their viewership. In the 1840s, when the authorities were concerned with the laxity of the commoners’ morals and sought to discourage preoccupation of townspeople with the Kabuki theater, artist Utagawa Kunisada depicted famous actors as a daimyo procession. Later, in 1868, when the Tokugawa government was about to fall and theater hardly posed any threat to the regime, Toyohara Kunichika, Utagawa Kunisada’s student, portrayed the members of the anti-shogunate forces under the guise of the Kabuki theater actors. Thus, by the irony of history, the concealable elements of the politically unwanted contents in ukiyo-e prints became reversed due to the changes in political situation, and hence, in censorship requirements.
Keywords: ukiyo-e prints; Utagawa Kunisada; Toyohara Kunichika; censorship; Kabuki theater actors; daimyo; anti-shogunal coalition